Research in Library and Information Science (As an Integral Part of Education in Information Science) - Gopinath, M. A. (Journal of Information and Knowledge, 1978)
States the objectives of professional education in L&IS and the mechanisms of achieving them; highlights the role of research as an innovative mechanism for learning. Traces of germination of research as an integral part of library and information science education in India at the Master's degree and the doctoral level. Discusses the topics of research input, indicating the shift in recent years from the technique, oriented developmental research to system-oriented research. Suggests joint research programmes in the utilization of developments in information technology for developing user-oriented information services in India.